The Known and Potential Intersections of Rab-GTPases in Human Papillomavirus Infections - Young, Jesse M.; Zine El Abidine, Amira; Gómez-Martinez, Ricardo A.; Ozbun, Michelle A. (Frontiers in Cell and Developmental Biology, 2019)
Papillomaviruses (PVs) were the first viruses recognized to cause tumors and cancers in mammalian hosts by Shope, nearly a century ago (Shope and Hurst, 1933). Over 40 years ago, zur Hausen first proposed that human papillomaviruses (HPVs) played a role in cervical cancer (zur Hausen, 1976); in 2008, he shared the Nobel Prize in Medicine for his abundant contributions demonstrating the etiology of HPVs in genital cancers. Despite effective vaccines and screening, HPV infection and morbidity remain a significant worldwide burden, with HPV infections and HPV-related cancers expected increase through 2040. Although HPVs have long-recognized roles in tumorigenesis and cancers, our understanding of the molecular mechanisms by which these viruses interact with cells and usurp cellular processes to initiate infections and produce progeny virions is limited. This is due to longstanding challenges in both obtaining well-characterized infectious virus stocks and modeling tissue-based infection and the replicative cycles in vitro. In the last 20 years, the development of methods to produce virus-like particles (VLPs) and pseudovirions (PsV) along with more physiologically relevant cell- and tissue-based models have facilitated progress in this area. However, many questions regarding HPV infection remain difficult to address experimentally and are, thus, unanswered. Although an obligatory cellular uptake receptor has yet to be identified for any PV species, Rab-GTPases contribute to HPV uptake and transport of viral genomes toward the nucleus. Here, we provide a general overview of the current HPV infection paradigm, the epithelial differentiation-dependent HPV replicative cycle, and review the specifics of how HPVs usurp Rab-related functions during infectious entry. We also suggest other potential interactions based on how HPVs alter cellular activities to complete their replicative-cycle in differentiating epithelium. Understanding how HPVs interface with Rab functions during their complex replicative cycle may provide insight for the development of therapeutic interventions, as current viral counter-measures are solely prophylactic and therapies for HPV positive individuals remain archaic and limited.